INFLUENCE OF QUESTIONING TECHNIQUES IN EFL CLASSES ON DEVELOPING STUDENTS’ CRITICAL THINKING SKILLS - Mustika, Nurika; Nurkamto, Joko; -, Suparno (International Online Journal of Education and Teaching, 2020)
Rapid changes in global education directly affect each education aspects including skills that should be mastered by students and teaching strategy used. Moreover, developments of education in the 21st century put stronger importance on Higher-Order Thinking Skills (HOTS) in which critical thinking skills include. In this case, the teacher’s questioning as a strategy promoting HOTS to cultivate critical thinking skills will be the concern of this research. The research aimed to examine the level of questions used by the teacher and its contributions to students’ critical thinking. The research was carried out using case study design in Senior High School in East Java. In obtaining the data, classroom observation, field notes, and interviews were employed. The results showed that the teacher used both low order questions and high order questions. Additionally, it was also found that lower-order thinking questions could not facilitate students to think critically, however, it only leads the students to understand the concept given. Hence, it was suggested to maximize the use of higher-order levels questions to train the students to think critically.